Situational support and information security behavioural intention: a comparative study using conservation of resources theory - Hong, Yuxiang; Xu, Mengyi; Furnell, Steven (Taylor & Francis, 2023)
The formation of information security behavioural intention (ISBI) can be complex and dynamic in different contexts. This paper aims to examine and compare different users’ ISBI formalisation mechanisms when dealing with their personal affairs (non-work users) and organisational affairs (work users). Drawing on two principles of Conservation of Resources (COR) theory (i.e. resource loss principle, and resource gain principle), we developed two models to examine how situational support affects ISBI formation. The results of a study of 432 non-worker users and 261 work users indicate a curvilinear relationship between situational support and ISBI through subjective norms and risk perception for non-worker users, whilst a linear relationship via subjective norms is found for worker users. This is the first time that COR has been applied to explain the formation of ISBI. The findings broaden the research scope of individuals’ ISBI by revealing how situational support affects the formalisation mechanism for different users in cross-contexts. The theoretical and practical implications of the findings and the future study are discussed.
Keywords: Information security behavioural intention; situational support; risk perception; subjective norms; conservation of resources theory; social exchange theory